Fault‐controlled lithospheric detachment of the volcanic southern South Atlantic rift. (12th March 2016) - Becker, Katharina; Tanner, David C.; Franke, Dieter; Krawczyk, Charlotte M.
Abstract: We present structural models of two exemplary conjugate seismic lines of the southernmost South Atlantic margins to examine their initial evolution, especially the seaward‐dipping reflectors (SDRs). Modeling illustrates the different structure and inclination angles of the SDRs, which therefore require different subsidence histories. Since typical symmetrical subsidence models are not applicable, we suggest a model with a westward‐dipping detachment fault that offsets the SDRs on the South American margin and we speculate on passively subsided SDRs on the South African margin. We propose a simple‐shear rifting mechanism to explain the initial break‐up of the South Atlantic. Key Points: We observe different inclination angles and structure of the SDRs in two conjugate sections across the South Atlantic margin Modeling suggests a detachment fault bounds the SDRs on the South American side We suggest a simple shear mechanism to explain the initial break‐up of the South Atlantic